The political psychology of globalization Muslims in the west - Kinnvall, Catarina; Nesbitt-Larking, Paul W. (Paul Wingfield) 1954- (Oxford University Press, 2011)
In an increasingly globalized world, there are new economic strategic, cultural, and political forces at work. This book explores how these shifts and shocks have influenced the way in which Muslim minorities in Western countries form their identities as political actors.